Sistem Pengupahan Pegawai Paroki dalam Perspektif Ensiklik Laborem Exercens Artikel 19: Tinjauan Manajemen Sumber Daya Manusia dan Ajaran Sosial Gereja - Gunawan, Theodorus Christian (Institutum Ioannis Mariae Vianney Surabayanum, 2024)
The Church is both a spiritual and secular institution; it is called spiritual because it contains religious practices that connect God and humans through sacramental celebrations, and it is called secular because it contains governance systems such as those that occur in organizations in general. One of the concerns that occurs in the Catholic Church is the existence of a wage system for parish employees that is still not appropriate. This paper will review the issue and try to examine the problem from the perspective of the Encyclical Laborem Exercens written by Pope John Paul II, specifically in Article 19. The review used in this paper is Human Resource Management and Social Teaching of the Church. This paper will attempt to understand the basic concepts of Human Resource Management and the Wage System of Parish Employees, then understand the elements of work spirituality and the ideas of Church Social Teaching in the Encyclical Laborem Exercens Article 19 on Wages, and finally review the extent to which the ideas in the Encyclical Laborem Exercens Article 19 can inspire the wage system of parish employees.